An evaluation of the use of Turnitin for electronic submission and marking and as a formative feedback tool from an educator's perspective. (4th June 2013) - Buckley, Emily; Cowap, Lisa
Abstract The aim of this project was to pilot plagiarism detection software and online marking, evaluating its use with staff on a first year undergraduate module within the psychology department at a UK university. One hundred and sixty undergraduate psychology students submitted three assignments via Turnitin, and staff used the software to check for instances of academic misconduct and marked submissions using the GradeMark feature in the software, providing online feedback to students. Eleven members of teaching staff took part in focus groups to gain insight into their experiences of using Turnitin in this manner, and this paper reports the findings. Results indicated that staff identified several strengths but also several weaknesses to the implementation of Turnitin and GradeMark. The OriginalityCheck feature received very positive evaluations due to its capacity to provide a clear and timely indicator of plagiarism levels in assignments and a useful formative learning tool for students from an educator perspective. Staff did however encounter some technical difficulties when using the software. In conclusion, for staff, the benefits of using Turnitin were clear, and it has the potential to be a very valuable asset to plagiarism detection and electronic marking.